Disturbances in Body-Based Mental and Motor Imagery in Anorexia and Bulimia Nervosa – A Systematic Review of Experimental Studies - Akansha M. Naraindas; Sarah M. Cooney (Journal of Experimental Psychopathology)
Imagining one’s body is crucial for how we perceive our appearance (i.e. imagining how we might appear to others), for imagining movement (motor imagery), navigation, and self-recognition. Mental body representations can be categorized into a perceptual component, known as the body image, and an action-related component, referred to as the body schema. A disturbed body image, involving altered perceptions and attitudes towards appearance, is a diagnostic feature of Anorexia Nervosa (AN) and Bulimia Nervosa (BN). The review identifies experimental paradigms used to measure body-based mental and motor imagery in individuals with AN and BN, investigating body representation beyond perceptual size and shape distortions compared to healthy controls. Three databases (PsycINFO, PubMed, and Embase) were searched, and 19 articles were included. Four characteristics of mental imagery were found to be distorted in individuals with AN and BN: body-scaling, imagined action, mental rotation, and spatial reference frame processing. Fourteen tasks were identified to assess these distortions in body-based mental imagery. This review highlights that altered body representations in AN and BN extend beyond conscious size and shape perceptions to include unconscious representations for movement and action planning. Future research should examine how body-based mental imagery sustains psychopathology in AN and BN.